Penguatan Penegakan Hukum Lingkungan di Indonesia: Tantangan dan Strategi Inovatif - Boby Rahman; Aldri Frinaldi; Dasman Lanin; Rembrandt; Mhd. Ridha (Journal of Innovative and Creativity, 2025)
Environmental law enforcement in Indonesia is grounded in a strong normative framework through Law No. 32 of 2009 on Environmental Protection and Management (UUPPLH). However, its effectiveness remains constrained by challenges in implementation. This study aims to analyze the dynamics of environmental law enforcement in Indonesia by examining the gap between legal norms and practice, institutional barriers, and potential innovations to enhance legal effectiveness. Employing a qualitative approach with a normative juridical method, the research draws on primary and secondary legal materials, including legislation, court decisions, and official environmental reports. The findings reveal that most environmental violations are still resolved through administrative sanctions, reflecting limitations in evidence, interagency coordination, and monitoring capacity. Nevertheless, reform efforts toward data-driven and transparent supervision have begun through initiatives such as the Continuous Emission Monitoring System (CEMS), Online Single Submission (OSS), and regional environmental incentive programs like PROPER. In conclusion, strengthening environmental law enforcement in Indonesia requires cross-sectoral collaboration and a paradigm shift from a punitive to a collaborative and adaptive approach to achieve ecologically just environmental governance.